2013
DOI: 10.1007/s10495-013-0809-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential autophagic cell death under stress with ectopic cytoplasmic and mitochondrial-specific PPP2R2B in human neuroblastoma cells

Abstract: Protein phosphatase 2A is one of four major classes of serine/threonine phosphatases. Overexpression of brain-specific regulatory subunit PPP2R2 in neuron cells is implicated in pathogenesis. The alternative splicing of PPP2R2B encodes two isoforms. They are subunit of cytoplasmic specific Bβ1 and mitochondria-targeted Bβ2. The two constructs were transfected into human neuroblastoma cells, SK-N-SH, respectively, and the stable clones overexpressing either Bβ1 or Bβ2 established. We have reported that Bβ2 clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…PP2A is a multifunctional heterotrimeric serine/threonine protein phosphatase composed of a scaffolding A subunit, a catalytic C subunit, and a regulatory B subunit, the latter of which is expressed as several distinct isoforms. For example, among B subunit isoforms, the brain-specific splice isoform Bβ2, upon neurotoxic stress, translocates from the cytosol to the outer mitochondrial membrane, triggered by phosphorylation of three N-terminal residues [85], to induce mitochondrial fission and to execute apoptosis [86], a process which is accompanied by increased ROS production [87]. Mitochondrial PP2A also provides a direct link to autophagy, which is induced in several disorders including neurodegenerative disease due to mitochondrial dysfunction or cellular stress and can further enhance cellular demise [88].…”
Section: Role Of Oxidative Phosphorylation In Acute Inflammationmentioning
confidence: 99%
“…PP2A is a multifunctional heterotrimeric serine/threonine protein phosphatase composed of a scaffolding A subunit, a catalytic C subunit, and a regulatory B subunit, the latter of which is expressed as several distinct isoforms. For example, among B subunit isoforms, the brain-specific splice isoform Bβ2, upon neurotoxic stress, translocates from the cytosol to the outer mitochondrial membrane, triggered by phosphorylation of three N-terminal residues [85], to induce mitochondrial fission and to execute apoptosis [86], a process which is accompanied by increased ROS production [87]. Mitochondrial PP2A also provides a direct link to autophagy, which is induced in several disorders including neurodegenerative disease due to mitochondrial dysfunction or cellular stress and can further enhance cellular demise [88].…”
Section: Role Of Oxidative Phosphorylation In Acute Inflammationmentioning
confidence: 99%
“…Although autophagy is a survival mechanism, it has also been suggested that autophagy could be cytotoxic when cells suffer treatment‐induced stress. Excessive cell damage will lead to autophagic cell death (Fang et al ., ; Li et al ., ). In the present study, we have investigated, in cancer cells the effects of tetrandrine‐induced stress in the presence of chloroquine, which prevents autophagy by blocking autophagosome fusion and degradation.…”
Section: Introductionmentioning
confidence: 99%